A Simple Throw Model for Frontal Vehicle-Pedestrian Collisions - Batista, Milan (Promet - Traffic&Transportation, 2008)
This paper discusses a simple theoretical throw model forfrontal vehicle-pedestrian collisions. The model is based on thesimple assumption that pedestrian movement after impact canbe approximated by the movement of a mass point. Two methodsof vehicle-pedestrian collision reconstruction are discussed:one knowing only the throw distance and the otherwhen also impact to ground contact distance is known. Themodel is verified by field data available in the literature and bycomportment with full scale numerical simulation.